Mathématiques
kholoudhfd
9

Ecrire plus simplement chaque produit . A= y x (-4) B= -y x 3 x (-15) C= 1,2 y x (-10) x (-4y) D= -1sur4 y x 8sur3 y calculer chacune de ces expression pour y = -2

+0
(2) Réponses
lamiloo

A= y x (-4)  A = -4y A(-2) = -4x-2 = 8 B= -y x 3 x (-15)  B = 45y B = 45x-2 = -90 C= 1,2 y x (-10) x (-4y)  C -12yx-4y C = 48y² C = 48x(-2)² = 48x4 = 192 D= -1sur4 y x 8sur3 y D = -1/4y x8/3y D = -2/3y² D = -2/3x(-2)² D = -1/6

clementchamoul

A= y x (-4)    = -4y B= -y x 3 x (-15)   = -3y x (-15)   = 45y C= 1,2y x (-10) x (-4y)   = -12y x (-4y)   = 48y² D= -1/4y x 8/3y   = -2/3y²

Ajouter une réponse